A Biotype of Annual Bluegrass (Poa annua) in Tennessee Is Resistant to Inhibitors of ALS and Photosystem II. Issue 1 (March 2015) - Brosnan, James T.; Breeden, Gregory K.; Vargas, Jose J.; Grier, Logan
Abstract : Annual bluegrass resistance to inhibitors of acetolactate synthase (ALS) and photosystem II (PSII) in managed turf has been confirmed in the southeastern United States. A biotype of annual bluegrass that had developed resistance (R) to the PSII inhibitor simazine was not controlled by POST applications of foramsulfuron or trifloxysulfuron in 2011 or 2012. In whole plant dose-response experiments, trifloxysulfuron, simazine, and indaziflam controlled a susceptible (S) population of annual bluegrass > 91% when applied POST to nontillering plants. However, trifloxysulfuron applications at 3.5 to 223 g ai ha −1 only controlled R annual bluegrass ≤ 40%. Similarly, simazine at 140 to 9, 000 g ai ha −1 only controlled R annual bluegrass ≤ 20%. R annual bluegrass plants were more tolerant to indaziflam applied POST to leaf stage plants prior to tillering, as rates > 100 g ai ha −1 were needed to control R annual bluegrass ≥ 96%. No differences in the activity of ALS in R and S plants exposed to increasing foramsulfuron concentrations from 0 to 100 µM were detected suggesting that nontarget mechanisms could explain reduced efficacy of POST herbicide applications in whole plant dose-response experiments. Applications of indaziflam (35 to 70 g ha −1 ) and oxadiazon (2, 240 to 4, 500 g ai ha −1 ) effectively controlled R annual bluegrass when applied PRE. This biotype of R annual bluegrass is the first reported instance of a weed developing resistance to multiple modes of action in managed turf. Education is needed among turf managers regarding the consequences of exclusive use of the same herbicides for annual bluegrass control leading to the onset of herbicide resistance.